Ð—Ð¼Ñ–Ð½Ð° Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ñ– Ð´ÐµÐ³Ñ–Ð´Ñ€Ð¾Ð³ÐµÐ½Ð°Ð·, Ð²Ð¼Ñ–ÑÑ‚Ñƒ Ð³Ð¾Ñ€Ð¼Ð¾Ð½Ñ–Ð² Ñ– ÑÑ‚Ð°Ð½Ñƒ Ð»Ñ–Ð¿Ð¾Ð¿ÐµÑ€Ð¾ÐºÑÐ¸Ð´Ð°Ñ†Ñ–Ñ— Ð² Ð°Ð»Ð¾Ð³ÐµÐ½Ð½Ñ–Ð¹ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ– Ð² Ð·Ð°Ð»ÐµÐ¶Ð½Ð¾ÑÑ‚Ñ– Ð²Ñ–Ð´ Ð´Ñ–Ñ— Ð½Ð¸Ð·ÑŒÐºÐ¸Ñ… Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€ - Grischenko, V. I.; Shepitâ€™ko, V. I.; Strona, V. I.; Yurchenko, T. M.; Ryazantsev, V. V.; Tsebrzhinsky, O. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The paper presented the data on metabolic alterations in placenta tissue during its hypothermic storage. The most manifested metabolic changes in placenta tissue were noted when being stored for 24hrs (4°C), 24hrs (-196°C) and further storage for 1 year (-20°C).